Congenital diaphragmatic hernia in neonate: A retrospective study about 28 observations - Rachid Khemakhem; Basma Haggui; Houda Rahay; Faouzi Nouira; Awatef Charieg; Sofiane Ghorbel; Mahdi Trifa; Said Jlidi; Sonia Ben Khalifa; Beji Chaouachi (Wolters Kluwer Medknow Publications, 2012)
Objective: Our purpose was to review our experience with congenital diaphragmatic hernia emphasizing diagnosis, management, and outcome. Study Design: We conducted a retrospective review of all cases of babies with congenital diaphragmatic hernia diagnosed and treated in our centre from 1998 to 2010. Results: There were 28 congenital diaphragmatic hernia cases, 13 girls and 15 boys with a mean weight birth of 3 kg. Three patients (10, 6% of cases) died within a few hours after admission. In the remaining cases, surgery was performed after a stabilization period of 2 days. The diaphragmatic defect was sitting in the posterolateral left in 23 cases and right in 2 cases. Its dimensions were on average 4,5 cm, tow cases of agenesis of the cupola were seen and required the placement of gortex prosthesis. The remaining cases are treated by direct closure of defect. Postoperative course was marked by an early death in context of respiratory distress in six cases and later with sepsis in tow cases. The outcome was favourable in 17 cases (60, 7%), despite the occurrence of sepsis in four cases and evisceration in two cases. Conclusions: Congenital diaphragmatic hernia remains a serious disease with high mortality and morbidity despite advances in prenatal diagnosis and neonatal resuscitation.